The Importance of Chronotope in Literature - Yusufovna, Kakharova Mohigul (CONVERSE Journal Communication Science, 2025)
This study explores the significance of chronotope in literature, focusing on its role in shaping the unity of time and space in narrative structures. The research aims to analyze how chronotope functions in literary texts, comparing the works of American author Jack London and Uzbek writer Abdulla Qahhor to demonstrate how different lexical units convey hidden meanings and influence reader perception. The study employs a literary analysis methodology, incorporating conceptual analysis, interpretation of literary texts, and comparative analysis of genre and style. It examines lexical choices, narrative structures, and symbolic representations to understand how authors construct chronotope to enhance storytelling and ideological impact. The findings indicate that chronotope plays a crucial role in literary composition by structuring the plot, guiding character actions, and shaping thematic development. In Jack London's "Martin Eden," the setting and working conditions reflect realism and social critique, while in Abdulla Qahhor's "Sarob," the protagonist's imagined landscapes serve as a metaphor for personal struggle and societal transformation. The study highlights that the linguistic and poetic elements used by authors contribute significantly to the reader's perception of time and space, reinforcing the artistic and ideological depth of the literary work.